2017
DOI: 10.1371/journal.pone.0189071
|View full text |Cite
|
Sign up to set email alerts
|

Variable manifestations, diverse seroreactivity and post-treatment persistence in non-human primates exposed to Borrelia burgdorferi by tick feeding

Abstract: The efficacy and accepted regimen of antibiotic treatment for Lyme disease has been a point of significant contention among physicians and patients. While experimental studies in animals have offered evidence of post-treatment persistence of Borrelia burgdorferi, variations in methodology, detection methods and limitations of the models have led to some uncertainty with respect to translation of these results to human infection. With all stages of clinical Lyme disease having previously been described in nonhu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
106
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(114 citation statements)
references
References 56 publications
7
106
0
1
Order By: Relevance
“…On the other hand, all saline-treated mice were culture-positive. Our studies (46, 47, 50) and those of others (45, 49, 81) in mice, dogs (29, 52) and non-human primates (53, 54) have all reached similar conclusions: spirochetes are persisting, but are paradoxically non-cultivable. It was suggested that the persisting remnants of B. burgdorferi in the tissues of infected mice after antimicrobial treatment is DNA or DNA-containing structures rather than live bacteria (76, 82, 83).…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…On the other hand, all saline-treated mice were culture-positive. Our studies (46, 47, 50) and those of others (45, 49, 81) in mice, dogs (29, 52) and non-human primates (53, 54) have all reached similar conclusions: spirochetes are persisting, but are paradoxically non-cultivable. It was suggested that the persisting remnants of B. burgdorferi in the tissues of infected mice after antimicrobial treatment is DNA or DNA-containing structures rather than live bacteria (76, 82, 83).…”
Section: Discussionsupporting
confidence: 83%
“…Our results indicate that disseminated spirochetes of two different B. burgdorferi strains can persist in mice at 12 and 18 months following antimicrobial treatment. Non-cultivable spirochetes persist in mice (93), dogs (29), and non-human primates (54) inoculated with alternate strains of B. burgdorferi , so we are confirming that persistence and resurgence are not unique to N40.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations